Urine dipstick test for diagnosing urinary tract infection - Syarifah Julinawati; Oke Rina; Rosmayanti Rosmayanti; Rafita Ramayati; Rusdidjas Rusdidjas (Paediatrica Indonesiana, 2013)
Background Urinary tract infection (UTI) is a common diseasein children. Approximately 3-5% of girls and 1 % of boys developa UTI. In children, prompt treatment is essential because UTImay be a risk factor for developing renal insufficiency or end stagerenal disease. Howevet; prompt treatment depends on having arapid diagnosis. Urine dipstick testis a useful and commonly usedbecause it is low cost and gives rapid results, compared to urinecultures for diagnosing UTis. However, the diagnostic accuracyof the urine dipstick test is debatable.Objective To compare urine dipstick test (leukocyte esterase,nitrite, and combined leukocyte es terase and nitrite) to urineculture for diagnosing UTis.Methods A diagnostic study was held in H. Adam Malik Hospitalfrom May to June 2010. There were 70 children aged 2 to 14years and recruited by consecutive sampling. Two midstreamurine specimens were collected from subjects after cleaning theexternal urethral orifice. The first specimen was used for urinedipstick testing for leukocyte esterase and nitrite. The secondurine specimen was cultured in the laboratory. Urinalysis forleukocyte esterase and nitrite studies were performed with freshand uncentrifuged urine. Leukocyte esteras e and nitrite causeda change in dipstick color apparent within 2 minutes. Urinalyseswere considered to be positive for UTI if either leukocyte esteraseor nitrite were positive. The results of urine culture were used asthe golden standard.Results The sensitivities of leukocyte esterase and nitratetests were 90 .5% and 73.8%, respectively. However, thesensitivity for combined leukocyte esterase and nitrite testwas 96.4%. Nitrite test was more specific (60.7%) than theleukocyte esterase test (39.3%). The specificity of both teststaken together was 64.3% . For leukocyte esterase alone, nitratealone, and the two combined the positive predictive values(PPV) were 69.1 %, 73.8%, and 64.3.%, respectively, and thenegative predictive values (NPV) were 73.3%, 60.7%, and96.4%, respectively.Conclusion Urine dipstick test for leukocyte esterase and nitritecombined may be a good alternative diagnostic test for UTis inchildren than leukocyte esterase or nitrite by themselves in areaswith limited resources.